Biodiesel Dari Limbah Ikan Baung (Mystus Nemurus) Dengan Katalis Padat H-Zeolit - Hadyan Sartoni; Syaiful Bahri; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Biodiesel is an alkyl esters of long chain fatty acids derived from fatty material such as animal fat. A research synthesis of biodiesel from waste fish oil of baung into biodiesel with a solid H-zeolite catalyst. In this research review of physical properties (density, viscosity and acid number), analyzing the chemical content of biodiesel, the influence of the molar ratio of methanol to fish oil baung the percentage of conversion and optimal transesterification catalyst in the transesterification reaction in biodiesel synthesis. 50 grams of fish oil, versus 1:6 methanol to oil molar, catalyst 10% of the weight of oil input into the biodiesel reactor and then the process of biodiesel synthesis performed on the operating conditions of 60 ° C temperature and stirring speed of 200 rpm for 200 minutes. The results showed that the optimum conversion catalyst with 10% methanol 1:5 molar ratio that is equal to 87.02%. Physical test results obtained by the density of 890 kg/m3, 5.48 cSt viscosity, acid number 0.7013 mg-koh/gr sample. Results of analysis of chemical constituents by GC-MS, obtained the dominant component in the catalyst biodiesel with 10% methanol 1:5 molar ratio was 51.03% oleic methyl ester, methyl ester palmitic 18.76%, 9.50% linoleic methyl ester, 4.46% stearic acid methyl ester, methyl ester 2.00% elaidic. Results obtained have characteristics approaching the characteristics of biodiesel Indonesian National Standard (SNI). Kata kunci : fish oil, Biodiesel, H-zeolite catalyst, transesterification